2006
DOI: 10.2500/ajr.2006.20.2855
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Absorption of Gentamicin Nasal Irrigations

Abstract: Gentamicin nasal irrigation may be systemically absorbed. Although the otologic consequences of this finding are questionable, patients receiving gentamicin nasal irrigations should be counseled regarding this hypothetical possibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 12 publications
1
32
0
Order By: Relevance
“…Twice-daily irrigation with gentamicin for 3 to 15 weeks caused low but measurable systemic absorption, with blood levels ranging from 0.3 to 0.7 mg/mL. 88 Sensorineural hearing loss was noted in 23% of patients with CF who had used frequent irrigations, 89 and for this reason, the author cautions against use of aminoglycosides for chronic administration, especially greater than once daily. Topical antibiotics can be administered with or without a nebulizer.…”
Section: Crs Relation To Asthma Severitymentioning
confidence: 97%
“…Twice-daily irrigation with gentamicin for 3 to 15 weeks caused low but measurable systemic absorption, with blood levels ranging from 0.3 to 0.7 mg/mL. 88 Sensorineural hearing loss was noted in 23% of patients with CF who had used frequent irrigations, 89 and for this reason, the author cautions against use of aminoglycosides for chronic administration, especially greater than once daily. Topical antibiotics can be administered with or without a nebulizer.…”
Section: Crs Relation To Asthma Severitymentioning
confidence: 97%
“…At previously reported concentrations of the respective antibiotics (150 µg/ml mupirocin, 80 µg/ml gentamicin) in the absence of SinuSurf, no growth was evident [5,6,7,8]. However, a 10-fold dilution of mupirocin and a 100-fold dilution of gentamicin yielded growth while the addition of SinuSurf to these dilutions eradicated growth (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Still thorough discussions regarding potential side-effects of topical antibiotics should be discussed with any patients with the offlabel usage. Whatley et al [20] identified systemic absorption for topical gentamicin irrigations in patients who had previous functional endoscopic sinus surgery (FESS).…”
Section: Topical Antibioticsmentioning
confidence: 99%